Modification of Polyamide Knitted Fabric using Different Zeolites - Ojsteršek Alenka (Tekstilec, 2017)
The aim of this research was to apply three different types of zeolites and the combination thereof in the form of a very fine powder, together with different chemicals and additives on polyamide knitted fabric according to an industrially acceptable exhaustion procedure in order to study changes in the morphology, optical properties and wettability of surfaces. Zeolites were analysed using Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and gas physiosorption. Additionally, the morphology of zeolite-coated surfaces was examined closely using SEM, while changes in molecular-chemical level were examined by means of IR spectroscopy. Optical properties were studied using CIE colour measurement and diffuse refl ectance profile determination, while the hydrophilic/hydrophobic character was examined using goniometry. The obtained results show the suitability of the employed exhaustion procedure, depending on the type of zeolite and the composition of the treatment bath. The results also provided evidence of the enhanced wettability of PA fabrics using 4A and 13X zeolites in combination with selected additives.